Characteristics of human leptospirosis in three different geographical and climatic zones of Vietnam: a hospital-based study. (July 2022) - Mai, Le Thi Phuong; Dung, Luu Phuong; Mai, Tran Ngoc Phuong; Hanh, Nguyen Thi My; Than, Phan Dang; Tran, Van Dinh; Quyet, Nguyen Tu; Hai, Hoang; Ngoc, Do Bich; Hai, Pham Thanh; Hoa, Luong Minh; Thu, Nguyen Thi; et al.
Highlights: Fairly high seroprevalence of Leptospira was found in Vietnam. The diversity of Leptospira serovars circulates in all geographical zones. More females were observed to be infected than males. Effective measures for disease prevention may be imperatively needed. Abstract: Background: To our knowledge, this study is the first report on the seroprevalence of human leptospirosis and its epidemiological profile in 3 different geographical and climatic zones of Vietnam. Methodology: A hospital-based surveillance in 11 public hospitals in 3 provinces in Vietnam enrolled 3, 815 patients with suspected leptospirosis. Two consecutive enzyme-linked immunosorbent assay IgM and a single microscopic aggregation test were applied at a 1:100 to 1:800 dilution for probable or confirmed cases. Results: The findings showed that of the 3, 815 suspected cases, 68 (1.8%) were Leptospira -confirmed and 248 (6.5%) probable cases, whereas more than a third were positive for acute ELISA-IgM sera. Furthermore, 20 different serovars were found, of which Wolffi (14.2%), Hebdomadis (13.8%), and Icterohaemorrhagiae (12.6%) were the most predominant. The ratio of probable and confirmed cases of leptospirosis between females and males was 1.4:1, and their clinical manifestation was not specific. Cases were more likely to be detected in groups that are farmers, pet raising or livestock farming, of working age, practicing either wading in mud or walking barefoot, or exposed to heavy rainfall. Conclusions: Analysis of human leptospirosis has indicated fairly high seroprevalence and diversity of Leptospira serovars circulating in all studied geographical zones in Vietnam. The findings suggest an imperative need for effective measures of disease prevention, especially in high-risk groups.